(untitled) (Intent Research Scientific Journal, 2023)
In this review of the literature, the resources of last ten years about the Epstein-Barr virus, its morphology, the diseases it causes, the diagnosis and treatment of the disease, and the innovative modern diagnostic methods for the diagnosis of the Epstein-Barr virus are widely covered. The development of innovative diagnostic methods and technical convenience have made it possible to detect Epstein-Barr virus early and prevent its spread among the population. For example, the new, modern forms of PCR such as thw real-time PCR (Real-Time PSR), immuno-PCR, Multiplex PCR, Long-range PCR and other innovative technologies are important in the diagnosis of Epstein-Barr virus.